Urea‐temperature phase diagrams capture the thermodynamics of denatured state expansion that accompany protein unfolding. (25th July 2013) - Tischer, Alexander; Auton, Matthew
Abstract: We have analyzed the thermodynamic properties of the von Willebrand factor (VWF) A3 domain using urea‐induced unfolding at variable temperature and thermal unfolding at variable urea concentrations to generate a phase diagram that quantitatively describes the equilibrium between native and denatured states. From this analysis, we were able to determine consistent thermodynamic parameters with various spectroscopic and calorimetric methods that define the urea–temperature parameter plane from cold denaturation to heat denaturation. Urea and thermal denaturation are experimentally reversible and independent of the thermal scan rate indicating that all transitions are at equilibrium and the van't Hoff and calorimetric enthalpies obtained from analysis of individual thermal transitions are equivalent demonstrating two‐state character. Global analysis of the urea–temperature phase diagram results in a significantly higher enthalpy of unfolding than obtained from analysis of individual thermal transitions and significant cross correlations describing the urea dependence of Δ H 0 and Δ C P 0 that define a complex temperature dependence of the m ‐value. Circular dichroism (CD) spectroscopy illustrates a large increase in secondary structure content of the urea‐denatured state as temperature increases and a loss of secondary structure in the thermally denatured state upon addition of urea. These structural changes in the denatured ensemble make up ∼40% of the total ellipticity change indicating a highly compact thermally denatured state. The difference between the thermodynamic parameters obtained from phase diagram analysis and those obtained from analysis of individual thermal transitions illustrates that phase diagrams capture both contributions to unfolding and denatured state expansion and by comparison are able to decipher these contributions.